2012
DOI: 10.1271/bbb.110952
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Eriodictyol on IgE/Ag-Induced Type I Hypersensitivity

Abstract: Mast cells are the principal effector cells involved in the allergic response, through the release of histamine. We investigated the effect of eriodictyol, derived from the painted maple and yerba santa, on mast cell degranulation and on an allergic response in an animal model. We also investigated its effect on the expression of the ceramide kinase (CERK) involved in calcium-dependent degranulation, and on ceramide activation by multiple cytokines. Eriodictyol suppressed the release of beta-hexosaminidase, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
0
10
0
2
Order By: Relevance
“…The doses of both eriodictyol (28) and green tea extract (29) in our study were determined as reference.…”
Section: Methodsmentioning
confidence: 99%
“…The doses of both eriodictyol (28) and green tea extract (29) in our study were determined as reference.…”
Section: Methodsmentioning
confidence: 99%
“…20 Preincubation of mast cells with anti-asthmatic drugs, cedrol, and CR-NLCs showed a dose-dependent inhibition of β-hexosaminidase release from compound 48/80-sensitized mast cells, indicating their mast cell stabilizing activity. Comparative analysis of SIs of the anti-asthmatic drug, cedrol, and CR-NLC-treated mast cells revealed highest SI of NLC-C 2 (29.8) followed by NLC-C 1 (23.6)  cromolyn sodium Figure 6 Penetration of coumarin-6-Nlc (cM-Nlc) in mast cells.…”
mentioning
confidence: 92%
“…Only a fraction of ~250,000 plant species have been studied for antiasthmatic activity till now. [14][15][16][17][18][19][20][21] WHO has reported that 80% people of world population believe in traditional medicine for their health management. 22 In our laboratory, we have screened a vast number of natural extract in the form of steam volatile oil in vitro for their inhibitory effect on mast cell degranulation and anaphylactic shock.…”
Section: Introductionmentioning
confidence: 99%
“…Several research groups have reported that eriodictyol, luteolin, and quercetin inhibited mast cell degranulation (Yoo et al, 2012;Kimata et al, 2000;Matsuda et al, 2002). Herein, we investigated the effect of genistein, daidzein, and equol on histamine release, another chemical mediator, from calcium ionophore-stimulated rat PEC.…”
Section: Resultsmentioning
confidence: 99%